Design and Enantiopure Synthesis of(R)-2-((2-Oxooxazolidin-5-yl)methyl)isoindoline-1,3-dione: A Key Precursor to Build 2-Oxazolidinone Class of Antibacterial Agents - T. Rajesh; P. Suryanarayana Reddy; M. Manidhar; M. Vijaya Lakshmi; G. Madhusudhan (E-Journal of Chemistry)
A new synthetic method for the preparation of high enantiopure (R)-2-((2-oxooxazolidin-5-yl)methyl)isoindoline-1,3-dione has been developed. The enantiopurity of the obtained (R)-2-((2-oxooxazolidin-5-yl)methyl) isoindoline-1,3-dione is established using chiral high performance liquid chromatography (HPLC) i.e. enantiomeric excess (ee) as 100%. One among the two proposed approaches, is succeeded in preparing enantiopure targeted chiral building block using (R)-2-(chloromethyl)oxirane ((R)-epichlorohydrin) as precursor. This heterocyclic 2-oxazolidinone moiety could be useful to prepare a series of antibacterial agents containing 2-oxazolidinone.